KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK PENGHASILAN: FAKTOR-FAKTOR YANG MEMPENGARUHI - Ahmad Ibnu Harahap; Muhammad Iqbal Baihaqi; Dini Vientiany (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research aims to identify factors that influence taxpayer compliance in paying income tax in Indonesia. Tax compliance is an important element for continued state revenue and economic stability. This research uses a quantitative survey method with questionnaires distributed to 300 registered taxpayers at the Jakarta Tax Service Office (KPP). The collected data was analyzed using multiple linear regression to identify significant factors. The research results revealed that factors such as understanding tax regulations, the quality of services provided by the tax authority, perceptions of the fairness of the tax system, and the taxpayer’s income level have an influence significant impact on tax compliance. Apart from that, tax sanctions and incentives also influence the level of taxpayer compliance. Based on these findings, it is recommended that tax authorities increase tax education and improve service quality to increase taxpayer compliance. This research contributes to the tax literature by providing a deeper understanding of the factors that influence tax compliance. The practical implications of this research can be used as a reference by policy makers in formulating strategies to increase tax compliance in Indonesia.